Correction: An adamantane-based COF: stability, adsorption capability, and behaviour as a catalyst and support for Pd and Au for the hydrogenation of nitrostyrene. Issue 24 (25th November 2016) - Trandafir, M. M.; Pop, L.; Hădade, N. D.; Florea, M.; Neațu, F.; Teodorescu, C. M.; Duraki, B.; van Bokhoven, J. A.; Grosu, I.; Pârvulescu, Vasile I.; Garcia, Hermenegildo
Abstract : Correction for 'An adamantane-based COF: stability, adsorption capability, and behaviour as a catalyst and support for Pd and Au for the hydrogenation of nitrostyrene' by M. M. Trandafir et al., Catal. Sci. Technol., 2016, 6, 8344–8354.